2019
DOI: 10.1177/1947603519862318
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fluvastatin on Indian Hedgehog Pathway in Endochondral Ossification

Abstract: Statins have demonstrated to be effective for treating chondrodysplasia and its effects were believed to be associated with the fibroblast growth factor receptor 3 (FGFR3). Statins promoted the degradation of FGFR3 in studies using disease-specific induced pluripotent stem cells and model mice, however, recent studies using normal chondrocytes reported that statins did not degrade FGFR3. In order to further investigate the effects of statins in endochondral ossification, this study examined the influence of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…We next applied 3-NPA to cultured metatarsal bones, which we and others have used as an ex vivo model of cartilage development and long bone growth 20,[37][38][39][40][41] . Considering metatarsal bone cultures might require a higher concentration of 3-NPA than the two-dimensional chondrocyte cultures in our in vitro study, we used 1.0 and 3.0 mM 3-NPA for adequate tissue penetration.…”
Section: Resultsmentioning
confidence: 99%
“…We next applied 3-NPA to cultured metatarsal bones, which we and others have used as an ex vivo model of cartilage development and long bone growth 20,[37][38][39][40][41] . Considering metatarsal bone cultures might require a higher concentration of 3-NPA than the two-dimensional chondrocyte cultures in our in vitro study, we used 1.0 and 3.0 mM 3-NPA for adequate tissue penetration.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we revealed the positive effects of fluvastatin on chondrogenic differentiation of hADMSCs in the absence of exogenous growth factors. Fluvastatin significantly induced BMP2, SOX9, ACAN and COL2A1 expressions and accumulated GAGs in the pellet of Statins were previously reported to promote chondrogenic differentiation of ATDC5 cells, an in vitro model of chondrogenic differentiation, and to rescue the chondrogenic differentiation ability of induced pluripotent stem (iPS) cells from patients with achondroplasia or thanatophoric dysplasia [29,30]. These studies proposed that the mechanism by which statins influence chondrogenic differentiation is related to the Indian Hedgehog pathway or fibroblast growth factor receptor 3 (FGFR3); however, it is not fully understood.…”
Section: Discussionmentioning
confidence: 97%